Application of the Inquiry Method with the Help of Pop-Up Book Media to Improve Learning Outcomes on the Theme of Sound Sources and Sound Properties of Class IV MIS Darul Falah Jawai District - Buniarti; Saumi Setyaningrum; Sahrani (PT FORMOSA CENDEKIA GLOBAL, 2022)
This research is motivated by the low learning outcomes of students in class IV MIS Darul Falah Jawai. The purpose of this study was to find out: 1) the process of applying the Inquiry Method with the Help of Pop-Up Boo Media to Improve Learning Outcomes on the Theme of Sound Sources and Sound Properties in Class IV MIS Darul Falah, Jawai District, 2022/2023 Academic Year, 2) learning outcomes students after the Application of the Inquiry Method with the Help of Pop-Up Boo Media to Improve Learning Outcomes on the Theme of Sound Sources and Sound Properties in Class IV MIS Darul Falah, Jawai District, Academic Year 2022/2023, 3) how much has the learning outcomes of students increased before and after the Application of the Inquiry Method with the Help of Pop-Up Boo Media to Improve Learning Outcomes on the Theme of Sound Sources and Sound Properties in Class IV MIS Darul Falah, Jawai District, 2022/2023 Academic Year. This research is a Classroom Action Research (CAR) with a quantitative approach to descriptive analysis. There are four stages of research starting from planning, action, observation and reflection. Data collection techniques used in the form of observation, tests and documentation. Data collection tools in the form of observation sheets, test sheets and documents as well as cellphone cameras. The results showed that: 1) the process of implementing the inquiry method with the help of pop-up book media in cycle I had a score of 81 out of a total score of 110, namely 73.64% in the good category and in cycle II it increased by 94.28% in the very good category with a score of 99 out of a total score of 105. 2) the average value of students in cycle I after using the inquiry method with the help of pop-up book media obtained a result of 75.06 with a percentage of 73% whose value has reached KKM (65) is in the category good and the average value of students in cycle II after using the pop-up book media-assisted inquiry method obtained a result of 83.96 with a percentage of 100% whose value has reached KKM (65) is in the special/maximum category, 3) there is an increase the learning outcomes before and after using the pop-up book media-assisted inquiry method show that from pre-cycle to cycle I increased by 60%, from cycle I to cycle II increased by 27% and n from pre cycle to cycle II experienced an increase of 87%